THE INNOVATIVE HEAT NOT BURN (HNB ) AND ORAL HEALTH - A NEW APPROACH - M. Răescu; C.N. Cumpătă; F. T. Dogaru; R. N. Voinea-Georgescu; M.J. Țuculina (Romanian Society of Oral Rehabilitation, 2022)
Oral health means general health. Usually, the oral abnormalities or diseases are related to the organism balance. This is the reason why we encourage people to maintain a good oral health. Starting with a daily hygiene, the preventive treatments and cessation we may obtain the winning aim of the microbial battle. Smoking combustible cigarettes is associated with socializing, pleasure and addiction but also involved in bad breath, halitosis, gingival and mucosal damage, tooth loss, periodontal disease, oral cancer. People smoke because they are addicted to nicotine but are harmed by other constituents of tobacco smoke. Quitting smoking is very difficult and most adults who smoke today will continue to smoke.